Can We Use Design Approaches to Increase Comfort and Reduce Suffering at End-of-Life: A Focused Literature Review. Issue 1 (June 2021) - Schwellnus, Meg; Trudel, Chantal; Orosz, Zsofia
End-of-life (EoL) care is often a difficult period for all involved: the person who is dying, their family and friends, and care providers. A review and analysis of literature on design for end-of-life care led to identifying common themes that may influence end-of-life experience, design categories which aim to support EoL care, and continuing challenges that may undermine EoL experience. An additional review researched impacts of the COVID-19 pandemic on EoL experiences. The results of both reviews are presented here, as well as some suggestions for future directions in EoL design.